Water Quality Assessment of Selected Wells in the Farmer-led Irrigation System in Anloga District, Volta Region, Ghana - Henry Evonameh Igbadun; Olufunke Cofie; Donatus Obiajulu ONWUEGBUNAM; Michael Adote Kpakpo-Sraha; Seifu TILAHUN (ABUAD Journal of Engineering Research and Development)
Increased groundwater extraction for irrigation is leading to the intrusion of saline seawater into many wells in some communities in Anloga District, Volta Region, Ghana, with resultant adverse effects on crop productivity. This study investigated the water quality of selected wells in four communities of the district for their suitability for irrigation. Water samples were collected from 10 representative wells, purposively selected out of 60, to determine the pH, electrical conductivity, total dissolved salt by means of a pH/EC/TDS/Temperature portable meter, and the concentrations of sodium, potassium, calcium, magnesium, sulphates, chlorides, bicarbonate and nitrate, using standard chemical laboratory procedures. The geochemical characterization of the sampled water sources was carried out using the Piper trilinear diagram, and revealed the dominance of Na-Cl facies of the groundwater in Tegbi, Whuti and Anyanui, suggesting seawater encroachment connected with groundwater abstraction. The water samples from wells in Woe indicated the Ca-Mg-Cl-SO4 mixed type and are considered suitable for irrigation. About 50% of the sampled wells could be classified under the high salinity-low sodium hazard (C3-S1), 20% are under very high salinity-medium sodium hazard (C4-S2), another 20% under very high salinity-high sodium hazard (C4-S3) and 10% under medium salinity-low sodium (C2-S1) classes. These wells are prone to salinity, and farmers’ discretion is recommended through the adoption of conditional use of the irrigation water such as growing of salt-tolerant crops.